Shedding light into the black box: a prospective longitudinal study identifying the CanMEDS roles of final year medical students’ on-ward activities - Bugaj, Till Johannes; Schmid, Carolin; Koechel, Ansgar; Stiepak, Jan; Gröner, Jan; Herzog, Wolfgang; Nikendei, Christoph (Medical teacher, 2017)
Introduction: To our best knowledge, a rigorous prospective analysis of final year medical students’ (FY medical students) activity profiles during workplace learning is lacking. The present study investigated the CanMEDS characteristics of all on-ward activities performed by internal medicine FY medical students. We tested the hypotheses that during FY medical student workplace training (I) routine activities are predominantly performed, while supervised, more complex activities are underrepresented with (II) FY medical students performing an insufficient number of autonomous activities and that (III) the CanMEDS roles of the Communicator and the Professional prevail.Methods: During the second and the sixth week of their final year trimester at the University of Heidelberg Medical Hospital, N = 34 FY medical students (73% female; mean age 26.4 ± 2.4) were asked to keep a detailed record of all their on-ward activities and to document the duration, mode of action (active versus passive; independent versus supervised), estimated relevance for later practice, and difficulty-level in specially designed activity logbooks. CanMEDS roles were assigned to the documented activities via post-hoc expert consensus.Results: About 4308 activities lasting a total of 2211.4 h were documented. Drawing blood (20.8%) was the most frequently documented medical activity followed by full admission procedures (9.6%). About 14.9% of the time was spent with non-medical activities. About 82.1% of all medical activities performed went unsupervised. The Communicator (42%), the Professional (38%), and the Collaborator (7%) were assigned as the top three CanMEDS roles.Conclusions: The results call for increased efforts in creating more authentic learning experiences for FY medical students shifting towards more complex, supervised tasks, and improved team integration.